To calculate the contact parameters and the friction forces in cylindrical sliding guide. - Вельбой, В.П.; Диха, М.О. (Problems of Tribology, 2016)
Conducted design analysis of contact parameters for cylindrical slide guide using Hertz in a wide range of sizes and materials. Established the acceptability of the values of the coefficients of friction for flat progressive pairs in the calculation of the cylindrical guides sliding within existing tolerances and fits of conjugate bodies. Keywords: cylindrical guide rail sliding, the consolidated coefficient of friction, contact pressure, contact angle.